Lime sulphur mineral oil and garlic extract to suppress dormancy of kiwi - Biasi, Luiz Antonio; Lipski, Bernardo; Silva, Éder David Borges da; Oliveira, Odirlei Raimundo de; Sachi, Adriana de Toni; Peressuti, Rafael Aparecido (Revista de Ciências Agroveterinárias, 2010)
This study aimed to examine the effect of lime sulphur (LS), mineral oil (MO) and garlic extract (GE) on budbreak of 'Bruno' kiwifruit. In the experiment with lime sulphur, 16 treatments in factorial design 4 x 4 (budbreak solutions x bud position) were tested. The solutions were: MO 6%; MO 6% + LS 10%; MO 6% + LS 20% and MO 6% + LS 30%. In the experiment with garlic extract, 28 treatments in factorial design 7 x 4 (budbreak solutions x bud position) were tested. The solutions were: control; MO 4%; MO 4% + GE 2%; MO 4% + GE 4%; MO 4% + GE 6%; MO 4% + GE 8% and MO 4% + GE 10%. Four buds at the shoot apical position were examined at different dates in both experiments. All buds with one visible leaf or more advanced phenological stages were considered like bud burst. Apical bud always showed the greatest percentage of bud sprouting in both experiments, forming a decreased scale until low buds. Lime sulphur did not promote budbreak of kiwifruit, showing the same effect presented by the treatment with only mineral oil. Garlic extract showed effect on budbreak of kiwifruit. The MO 4% + GE 10% treatment was superior to the others, but it was not different from MO 4% + GE 6% and MO 4% + GE 8%. This superiority was a consequence of higher lateral buds sprouting, because apical buds sprouting were the same, averaging 93.33%. In conclusion, the lime sulphur until 30% of concentration combined with mineral oil 6% had no effect to budbreak of Bruno Kiwifruit. Conversely, the garlic extract at 10% of concentration combined with mineral oil 4% enhanced the percentage of lateral buds sprouting, but not in satisfactory levels.